2018
DOI: 10.1155/2018/5853474
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Massage-Inspired Haptic Device for Interpersonal Connection in Long-Distance Communication

Abstract: The use of tactile senses in mediated communication has generated considerable research interest in past decades. Since massage is a common practice in Asian cultures, we propose to introduce massage-based interactions in mediated communication between people in a close relationship. We designed a device for distant interactive massage to be used during online conversation and we assessed its effect on interpersonal connection with eight pairs of Chinese participants in romantic relationships. All pairs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Participants could either send (through the manipulation of a shoulder-like device) or receive (through vibrotactile stimulation) massages. The inclusion of touch increased the perceived emotional and physical connection within the couples (Haritaipan et al, 2018). Despite all the potential benefits, the implementation of interpersonal tactile devices in VR also raises some risks and ethical issues that should be carefully considered.…”
Section: Bringing Interpersonal Affective Touch Into Virtual Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…Participants could either send (through the manipulation of a shoulder-like device) or receive (through vibrotactile stimulation) massages. The inclusion of touch increased the perceived emotional and physical connection within the couples (Haritaipan et al, 2018). Despite all the potential benefits, the implementation of interpersonal tactile devices in VR also raises some risks and ethical issues that should be carefully considered.…”
Section: Bringing Interpersonal Affective Touch Into Virtual Realitymentioning
confidence: 99%
“…Participants could either send (through the manipulation of a shoulder-like device) or receive (through vibrotactile stimulation) massages. The inclusion of touch increased the perceived emotional and physical connection within the couples ( Haritaipan et al, 2018 ).…”
Section: Interactive Technologies: Do They Connect or Disconnect?mentioning
confidence: 99%
“…[ 12 ] Efforts to understand the vibratory characteristics of sensorimotor functions of the skin and to develop materials and skin‐like systems for vibratory inputs across all regions of the body will lead to profound advances in technologies for VR/AR, with applications that range from virtual social engagements, immersive gaming/entertainment experiences and interactive learning, to remote protocols for medical diagnosis, treatment, training, and rehabilitation, to interactive human–machine interfaces. [ 13–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…The human operators are aimed to accord the sense of touch in such teleoperation scenarios, in order to make them feel that they are manipulating the objects and environment like they interact with the real-world objects with their own hands. In a few cases, the patients who lost their touch sensation in any disease or accident injury this study has suggested for replacing the sense of touch [11] [12] [13]. Many people lose the sense of touch if an upper-limb amputee is lost because of loss of a hand [14].…”
Section: Introductionmentioning
confidence: 99%